Development of Student’s Musical Creative Thinking by Applying Musical Improvisation - Daugėlienė, Jūratė; Strakšienė, Diana (Pedagogika, 2017)
The article deals with experience of Music Pedagogy 2nd cycle 1st year students’ (N = 7) experimental activities. Development of musical creative thinking is the object of the research. The research aim is to reveal opportunities for development of musical creative thinking by applying musical improvisation. During the experiment organised under natural conditions, educational methods grounding on postulates of philosophical doctrines, such as postmodernism and constructivism, have been applied. Research methods: theoretical analysis of scientific literature; natural educational experiment; statistical analysis of the research data employing descriptive statistics. By employing improvisation, students were encouraged for musical creation. The prepared diagnostic instruments enabled to compare the changes in improvisation, musical creative thinking of the surveyed that took place during the experimental education. Factual material allowing to state that musical improvisation can contribute to development of musical creative thinking has been obtained. After the educational activities, students demonstrated a higher level of musical creative thinking which manifested through originality of improvisation, fields of melodic, rhythmic, harmonic, stylistic priorities. Musical improvisation is an effective factor for stimulation of musical creative thinking that can essentially enrich music teaching, learning and music performance in various music-related contexts.